2017
DOI: 10.1080/15440478.2017.1414651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture in Flax Fibres on the Quality of their Composites

Abstract: Moisture present in plant fibres is considered to be detrimental to the performance of composites. In general, a drying stage is performed on the plant fibre fabrics before manufacturing the composites since it is seemed to allow better output. This work provides an analysis about the effect of moisture in flax fibres on the overall quality of epoxy/flax biocomposites. Flax fibre fabrics were conditioned at different relative humidity (RH) environments and composites were manufactured by vacuum infusion techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 45 publications
3
34
0
2
Order By: Relevance
“…More than 10% of the air's moisture content can be absorbed by flax fibers within one hour at 90% RH. These results are quite consistent with a recent study 44 , where researchers found equilibrium moisture absorption is almost double (14.3%) at 95% RH than that at 70% RH. Interestingly, all the fibers reached the equilibrium moisture content at ambient temperature within 60 minutes regardless of the RH value ( Figure 6).…”
Section: Moisture Absorption Of Flax Fiberssupporting
confidence: 93%
“…More than 10% of the air's moisture content can be absorbed by flax fibers within one hour at 90% RH. These results are quite consistent with a recent study 44 , where researchers found equilibrium moisture absorption is almost double (14.3%) at 95% RH than that at 70% RH. Interestingly, all the fibers reached the equilibrium moisture content at ambient temperature within 60 minutes regardless of the RH value ( Figure 6).…”
Section: Moisture Absorption Of Flax Fiberssupporting
confidence: 93%
“…A des taux d'humidité é levé s, l'augmentation importante de la teneur en eau du composite peut ê tre corré lé e avec un comportement similaire des fibres de chanvre. Un comportement similaire a é té observé dans la litté rature sur des fibres cellulosiques et attribué aux phénomènes d'agglomération des molécules d'eau de par la pré sence de forces de tension de surface au sein des capillarité s [17,18].…”
Section: Isothermes De Sorptionunclassified
“…Le module tangent d'un maté riau composite dé pendant fortement des proprié té s de ses composants et le polypropylè ne n'é tant pas sensible à l'humidité , la variation observé e ici ê tre due à l'é volution des proprié té s des fibres vé gé tales et notamment au ramollissement causé par l'humidité . Des variations similaires ont é té dé crites dans la litté rature pour des fibres de lin [42] ainsi que des composites unidirectionnels renforcé s par des fibres de lin [43]. Par consé quent, la dé formation augmente avec la diminution du module tangent avec la plastification des fibres de lin et du glissement du ré seau fibreux.…”
Section: Hygroexpansionunclassified